S112. EFFECT OF CHRONIC LURASIDONE TREATMENT ON CHRONIC MILD STRESS-INDUCED BEHAVIORAL DEFICITS: THE POTENTIAL ROLE FOR GLUCOCORTICOID RECEPTOR SIGNALING - Calabrese, Francesca (Schizophr Bull, 2019)
BACKGROUND: Psychiatric diseases are characterized by an altered function of the hypothalamic-pituitary-adrenal axis. The activation of this system is also involved in learning and memory processes and its dysregulation may therefore contribute to different psychopathologic domains, including cognitive deficits. On these bases, the aim of this study was to investigate the potential involvement of genomic and non-genomic glucocorticoid receptor (GR) signaling in the behavioral alterations induced by the chronic mild stress (CMS) paradigm in rats. Under this scenario, we also investigated the ability of the novel antipsychotic lurasidone in normalizing the behavioral and molecular changes produced by CMS. METHODS: Adult male Wistar rats were exposed to CMS for 2 weeks and sucrose consumption was used to identify the rats susceptible to the stress protocol. Animals were then randomized to receive vehicle or lurasidone for 5 weeks while continuing the stress procedure. During the 7 weeks of stress protocol rats were tested for anhedonia and at the end of the CMS, animals were exposed to the novel object recognition test (NOR), before being sacrificed for the dissection of the brain regions to be investigated at molecular level. RESULTS: Exposure to 7 weeks of CMS produced an anhedonic phenotype as well as cognitive impairment in the NOR test and these abnormalities were normalized by chronic lurasidone treatment. At molecular level, CMS rats show an increase of GR protein levels in the membrane compartment of the dorsal hippocampus, which was paralleled by an up-regulation of the phosphorylation in Ser603 of SINAPSYN Ia/b, a protein enriched in the presynaptic compartment, and by an increase of the mitochondrial marker Cox3. Moreover, exposure to the NOR test induced nuclear translocation of GRs in control (non-stressed) rats, which was associated with an upregulation of GR-transcriptional activity, as demonstrated by increased mRNA levels for Gadd45β, Sgk-1 and Nr4a1 mRNA. Interestingly such mechanisms were impaired in CMS rats, but they were completely normalized following prolonged lurasidone treatment. DISCUSSION: In summary, our results suggest that exposure to CMS produces complex changes in GR function and signaling, which may contribute to the behavioral abnormalities (anhedonia and cognitive impairment) found in stressed rats. The ability of chronic lurasidone to normalize such alterations provides further support on the potential of this novel antipsychotic to counteract molecular and functional changes that contribute to different domains of psychiatric disorders.